2014
DOI: 10.1007/s13353-014-0215-z
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotides replacing the roles of repetitive sequences pAs1, pSc119.2, pTa-535, pTa71, CCS1, and pAWRC.1 for FISH analysis

Abstract: Hybrids derived from wheat (Triticum aestivum L.) × rye (Secale cereale L.) have been widely studied because of their important roles in wheat cultivar improvement. Repetitive sequences pAs1, pSc119.2, pTa-535, pTa71, CCS1, and pAWRC.1 are usually used as probes in fluorescence in situ hybridization (FISH) analysis of wheat, rye, and hybrids derived from wheat × rye. Usually, some of these repetitive sequences for FISH analysis were needed to be amplified from a bacterial plasmid, extracted from bacterial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
336
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 346 publications
(347 citation statements)
references
References 39 publications
6
336
1
4
Order By: Relevance
“…The chromosome preparations were mounted in propidium iodide dissolved in Vectashield antifade solution (Vector Laboratories, Burlingame, CA, USA). The FISH method was based on the protocol described by Tang et al (2014). Oligo-pSc119.2-1 repeats were end-labelled with 6-carboxyfluorescein (6-FAM), whereas oligo-pTa535-1 and (GAA)7 were labelled with 6-carboxytetramethylrhodamine.…”
Section: Genomic and Fluorescence In Situ Hybridisation (Gish And Fish)mentioning
confidence: 99%
See 1 more Smart Citation
“…The chromosome preparations were mounted in propidium iodide dissolved in Vectashield antifade solution (Vector Laboratories, Burlingame, CA, USA). The FISH method was based on the protocol described by Tang et al (2014). Oligo-pSc119.2-1 repeats were end-labelled with 6-carboxyfluorescein (6-FAM), whereas oligo-pTa535-1 and (GAA)7 were labelled with 6-carboxytetramethylrhodamine.…”
Section: Genomic and Fluorescence In Situ Hybridisation (Gish And Fish)mentioning
confidence: 99%
“…6a). Probing with pTa535, a sequence which discriminates D genome chromosomes from those of A and B, and with pSc119.2, which preferentially hybridises to the B and R genome chromosomes (Tang et al 2014), showed that the Xiaoyanmai 7 genome lacks six of the seven D genome chromosomes (the exception was chromosome 2D), and that these have been replaced by six pairs of homoeologous rye chromosomes (Fig. 6a).…”
Section: The Xiaoyanmai 7 Karyotype As Visualised By In Situ Hybridismentioning
confidence: 99%
“…Cereal Research Communications 44, 2016 TATTACTCA CCGCTTTGGGGTCCCATAGCTAT-3') and oligo-pTa535-1 (Tamra-5'-AAAAACTTGACG CACGTCACGTACAAATTGGACAAACTCTTTCGGAGTAT-CAGGGTTTC-3') were prepared and fluorescence in situ hybridization (FISH) were done as described previously (Tang et al 2014). Slides were examined on an Olympus BX-51 fluorescence microscope.…”
Section: Cytological Observationsmentioning
confidence: 99%
“…Oligonucleotide probes end-labelled with 6-carboxyfluorescein (6-FAM) or 6-carboxytetramethylrhodamine (Tamra) are usually used in multi-colour FISH analysis to distinguish wheat A-, B-, and D-genome chromosomes and wild relative species of wheat (Tang et al 2014). Probes oligo-pSc119.2-1 and oligo-pTa535-1 were used to identify chromosomes in line 12-5-1.…”
Section: Fish Analysis Of 12-5-1mentioning
confidence: 99%
See 1 more Smart Citation